Embryological development of the intestine and necrotizing enterocolitis - Anna De Magistris; Maria Antonietta Marcialis; Melania Puddu; Angelica Dessì; Roberta Irmesi; Elisabetta Coni; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2016)
It is possible to distinguish two phases in the development and maturation of the intestine: intra-uterine and extra-uterine. Up until the 13th week of the embryological phase, a fetus' development is not controlled by factors external to the alimentary canal. It is instead guided by the homeotic genes that control the proliferation and differentiation during the embryogenesis.      A fetus' interaction with the external environment starts with the perforation of the buccal membrane, when the fetus starts swallowing the amniotic fluid. Both in pathological and physiological conditions, the encounter with the microbiota - that surely happens at birth, but could happen before as well - furnishes to the developing intestine elements which are necessary and essential to the growth of the organ, the barrier function, and the specific and nonspecific immunity. The link between development, maturation and inflammation is very important and influences the entire intestinal homeostasis. In case of preterm birth, the immaturity of the system creates a proinflammatory environment where the tolerance of the commensal microbiota cannot be taken for granted, and the maternal milk is not always available. These grounds are preconditions for the Necrotizing Enterocolitis (NEC). NEC is a calamitous pathology for a preterm baby, able to increase mortality, morbidity and the length of hospitalization. This review aims at understanding how to prevent NEC. It will do so by analyzing the mechanisms of the development of the inflammation at intestinal level, and at the level of its regulation. Several evidences, both clinical and experimental, show that the main form of NEC prevention is the dispensation of maternal milk. Maternal milk allows a proper growth and development of the intestine, a proper settlement of the microbiota, and control over the intestinal inflammation.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano